The little book of HTML/CSS coding guidelines - Meiert, Jens Oliver (O'Reilly Media, 2015)
A proper plan can improve your code, including your HTML documents and CSS style sheets. Jens Oliver Meiert explores the theory and practice of coding guidelines and shows, using Google's HTML and CSS standards as a particular example, how consistency and care can make the code base you create today much easier to deal with when you-or someone else-work on it later. Jens Oliver Meiert is a former senior developer and tech lead at Google, Aperto, and GMX, where he architected internal frameworks that married fast development with high quality code.